'Postage-stamp PIV': small velocity fields at 400 kHz for turbulence spectra measurements. (16th February 2018) - Beresh, Steven J; Henfling, John F; Spillers, Russell W; Spitzer, Seth M
Abstract: Time-resolved particle image velocimetry recently has been demonstrated in high-speed flows using a pulse-burst laser at repetition rates reaching 50 kHz. Turbulent behavior can be measured at still higher frequencies if the field of view is greatly reduced and lower laser pulse energy is accepted. Current technology allows image acquisition at 400 kHz for sequences exceeding 4000 frames but for an array of only 128  ×  120 pixels, giving the moniker of 'postage-stamp PIV'. The technique has been tested far downstream of a supersonic jet exhausting into a transonic crossflow. Two-component measurements appear valid until 120 kHz, at which point a noise floor emerges whose magnitude is dependent on the reduction of peak locking. Stereoscopic measurement offers three-component data for turbulent kinetic energy spectra, but exhibits a reduced signal bandwidth and higher noise in the out-of-plane component due to the oblique camera images. The resulting spectra reveal two regions exhibiting power-law dependence describing the turbulent decay. The frequency response of the present measurement configuration exceeds nearly all previous velocimetry measurements in high speed flow.